Dissecting the Inorganic Nanoparticle-Driven Interferences on Adhesome Dynamics - Vladimir Mulens-Arias (Journal of Nanotheranostics, 2021)
Inorganic nanoparticles have emerged as an attractive theranostic tool applied to different pathologies such as cancer. However, the increment in inorganic nanoparticle application in biomedicine has prompted the scientific community to assess their potential toxicities, often preventing them from entering clinical settings. Cytoskeleton network and the related adhesomes nest are present in most cellular processes such as proliferation, migration, and cell death. The nanoparticle treatment can interfere with the cytoskeleton and adhesome dynamics, thus inflicting cellular damage. Therefore, it is crucial dissecting the molecular mechanisms involved in nanoparticle cytotoxicity. This review will briefly address the main characteristics of different adhesion structures and focus on the most relevant effects of inorganic nanoparticles with biomedical potential on cellular adhesome dynamics. Besides, the review put into perspective the use of inorganic nanoparticles for cytoskeleton targeting or study as a versatile tool. The dissection of the molecular mechanisms involved in the nanoparticle-driven interference of adhesome dynamics will facilitate the future development of nanotheranostics targeting cytoskeleton and adhesomes to tackle several diseases, such as cancer.